Isolation and Characterization of Potential Antibiotic-Producing Actinomycetes from Water and Soil Sediments of Different Regions of Nepal. (3rd March 2021) - Shrestha, Bhanu; Nath, Dharmendra Kumar; Maharjan, Alina; Poudel, Anju; Pradhan, Roshani Nhuchhen; Aryal, Sagar
Abstract : Introduction . The actinomycetes are diversely distributed microorganisms in nature. The geographical diversity of Nepal is suitable for adaptation of various species of actinomycetes. The distribution of the actinomycetes is dependent upon the altitude and nature of the soil and water. Methods . A total of 22 water and soil samples were collected from different regions of Nepal and were processed. Different isolates were characterized by observing colony characteristics and microscopic characteristics. Screening of the antimicrobial property was based upon perpendicular line streaking and submerged-state fermentation for antibiotic production. Results . From the identification tool used, 12 were found to be Micromonospora, 9 were Nocardia, and 7 were Streptomyces. Out of total samples, 8 isolates of actinomycetes were tested effective against the tested bacteria by primary screening using the well diffusion method. Among the primarily screened, all isolates were subjected to submerged-state fermentation methods to produce crude extracts and 4 were found to be effective against the tested bacterial group. The actinomycetes identified from a water source showed better antimicrobial property towards the tested bacteria than the soil sample. Most isolates were found to be Micromonospora followed by Nocardia and Streptomyces with higher antimicrobial activities. Conclusion . The water source and soil sediments of Nepal provide suitable environments for actinomycetes towards obtaining a novel antimicrobial agent. The study of actinomycetes from various unexploited areas of Nepal is necessary. Thus, exploitation of various regions of Nepal for the discovery of an effective antimicrobial agent is helpful in providing a solution to the cost-effective therapy and action against antibiotic resistance.